(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study explores the current state of AA Trading and Construction’s ordering system. Through interviews, it was found that there are issues with their delivery and ordering processes. The organization has a trained workforce that prioritizes customer satisfaction and promotes public trade services with high-quality materials. The researchers suggest additional truck support, quality and material inspections, social media channels, and consolidating order channels to improve their services. The researchers conducted a qualitative study through face-to-face interviews, email and Facebook communication, and surveys. The study aims to provide helpful suggestions for improving AA Trading and Construction’s ordering and delivery processes. Based on the findings, the researchers recommend additional trucks for the company and using social media channels with a consolidated approach. Quality assurance and material inspection during the ordering and delivery process are also suggested to ensure that the organizational product or service meets the specifications and is dependable. The researchers believe implementing these procedures will lead to a more efficient and streamlined process for AA Trading and Construction, allowing them to grow without sacrificing customer satisfaction.